Development of a Fork-Shaped Neural Interface with High Spatial Selectivity for Bidirectional Peripheral Nerve Stimulation and Recording - Choi, Wonsuk; Park, HyungDal; Oh, SungHwan; Hong, Jeong-Hyun; Kim, Junesun; Yoon, Dae sung; KIM, JIN SEOK (제27회 한국 MEMS 학술대회 (2025 마이크로나노시스템학회 춘계 학술대회), 2025)
This study develops and validates a multi-intrafascicular shank array neural interface with fork-shaped spirally for peripheral nerves, optimizing spatial resolution, functional specificity, and charge storage. The 32-channel electrode array features low impedance and a guide for precise neuronal targeting. Over eight weeks, bipolar stimulation in two rats evoked muscle movements in 78.5% and 62.5% of regions post-implantation, with spatial resolution improving to 67.8% and 69.6% by week 8. The device maintained stable impedance and recorded signals, with 31.2% of channels detecting five distinct lower-limb signals in week 4. This neural interface advances neuroanatomical mapping, motor-sensory decoding, and has applications in bionic prosthetics and therapies, enhancing our understanding of peripheral nerve dynamics.